(3TQM bUjOI (B( (3HGfJ SYGO (B)s - (3dCHi GdHQcGJ ceGd GdOjf YHO GdQMef Hf eMeO GdCfHGQis; (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s
(3ChdgG (B:s
(3hHYO abO TQMJ ai gPg GdChQGb bUjOI cYH Hf RgjQ GdJi eOM HgG GdfHi Udi Gddg Ydjg hSde TQMkG dWjakG jSgd JCedg hjbQH JfGhdg s
(3BNQgG (B:s
(3cCfg ef bhdge (B: (3VMi jVMi EPG HQR ddTeS Ci dedGeSI LdOgG dG jKHJ Ydjg bQGO hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B226s
Keywords: (3GdCOHs